2020
DOI: 10.1142/s0218126621501206
|View full text |Cite
|
Sign up to set email alerts
|

Delay-Sensitive Network Selection and Offloading in LTE-A and Wi-Fi Heterogeneous Networks

Abstract: LTE-Advanced (LTE-A) offloading is concerned about alleviating traffic congestion for the LTE-A network, which includes the core network and the radio access network (RAN). Due to the scarcity of the radio resource, offloading for the LTE-A RAN is more critical, for which an efficient way is to integrate Wi-Fi with LTE-A to form a heterogeneous RAN environment. An LTE-A UE (User Equipment) with the wi-fi interface can therefore access the Internet via an LTE-A base station of Evolved Node B (eNB) or a wi-fi Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The LTE-A can achieve the maximum data rates of 1 Gbps in downlink and 500 Mbps in uplink for mobile users without movement; moreover, it can support up to 100 Mbps during high mobility (e.g., in a high-speed train). In the field of 4G/5G wireless network research, the research on the scheduling of various MAC layer networks has always been the focus of many researchers, such as the research on handover scheduling in heterogeneous mobile networks [5,6] and research on multimode Quality of Service (QoS) guarantee [7][8][9].…”
Section: Related Workmentioning
confidence: 99%
“…The LTE-A can achieve the maximum data rates of 1 Gbps in downlink and 500 Mbps in uplink for mobile users without movement; moreover, it can support up to 100 Mbps during high mobility (e.g., in a high-speed train). In the field of 4G/5G wireless network research, the research on the scheduling of various MAC layer networks has always been the focus of many researchers, such as the research on handover scheduling in heterogeneous mobile networks [5,6] and research on multimode Quality of Service (QoS) guarantee [7][8][9].…”
Section: Related Workmentioning
confidence: 99%
“…In the 4G/5G wireless broadband network research, the research on the scheduling of various MAC layer networks has always been the focus of many researchers, such as the research on handover scheduling in homogeneous or heterogeneous mobile networks [12][13][14] and research on multimode QoS guarantee [15][16][17][18]. In LTE-A mobile network scheduling research fields, some research studies focus on the discussion of uplink scheduling [19][20][21], but most of the research studies focus on downlink scheduling.…”
Section: Related Researchmentioning
confidence: 99%
“…They showed that the proposed algorithm reduces the number of handovers and improves the QoE experienced by users. Authors of [16] considered the LTE-A offloading to Wi-Fi. The authors proposed a network selection and offloading scheme based on the queueing model of M/G/1 in order to satisfy the delay budget of UEs and the global load balancing.…”
Section: Introductionmentioning
confidence: 99%